Characterization of the Megavoltage Cone-Beam Computed Tomography (MV-CBCT) System on HalcyonTM for IGRT: Image Quality Benchmark, Clinical Performance, and Organ Doses - Malajovich, Irina; Teo, Boon-Keng Kevin; Petroccia, Heather; Metz, James M.; Dong, Lei; Li, Taoran (Frontiers in Oncology, 2019)
Purpose: The Varian Halcyon includes an ultrafast 6MV flattening filter free (FFF) cone-beam computed tomography (MV-CBCT). Although a kV-CBCT add-on is available, in the basic configuration MV is used for image guided radiotherapy (IGRT). We characterized the MV-CBCT imager in terms of reproducibility, linearity, field of view (FOV) dependence, detectability of soft-tissue, and the effect of metal implants. The performance of the MV CBCT in the clinic, including resulting dose to organs, is also discussed herein. Methods: A Gammex phantom was scanned using a Halcyon MV-CBCT and a 120kVp Siemens Definition Edge CT. Mean and standard deviation of Hounsfield Units (HUs) for different electron density relative to water (ρₑᵂ) inserts were extracted. Doses to clinical patients due to MV-CBCT are calculated within Eclipse during treatment planning. Results: A stable and near-linear HU-to-ρₑᵂ curve was obtained using the MV-CBCT. As the scan length increased from 10cm to 28cm, the linearity of curve improved while the mean HUs decreased by 30%. All soft tissue inserts in the Gammex phantom were distinguishable. A crescent artifact affected HU measurements by up to 40 HUs. Soft-tissue contrast was sufficient for clinical online image guidance in the low dose (5MU) mode. Mean doses per fraction to organs-at-risk (OARs) were as high as 6cGy for head and neck, 5cGy for breast, and 4cGy for pelvis patients. Metal rods did not affect HU values or introduce noticeable artifacts. Conclusions: Halcyon’s MV-CBCT has sufficient soft tissue contrast for IGRT and lacks metal induced artifacts. Even though the absolute HU values vary with phantom size and scanning length, the HU-to-ρₑᵂ conversions are linear and stable day to day. In clinical cases, highest tissue doses from MV-CBCT ranged from 2-7cGy per fraction for various treatment sites, which could be significant for some organs at risk. Dose to out of treatment field organs can be limited by reducing the scan length definition during planning and using the low dose mode. The high quality imaging mode did not provide material advantages over the low dose mode. Adequate IGRT was successfully delivered to multiple tumor sites using MV-CBCT.